Methodological Evaluation of the Final Examinations of Medicine, Dentistry and Nursing - Margarita Rosa Romeu Escobar; Jose Aurelio Díaz Quiñones (Medisur)
Background: there are no studies providing an overview of the strengths and weaknesses in the design of final examinations in the medical university of Cienfuegos; consequently, it is unknown to what extent the recommendations for constructing those exams are met. Objective: to evaluate methodological aspects of the final examinations of Medicine, Dentistry and Nursing. Methods: a descriptive study was conducted at the medical university of Cienfuegos during the 2012/2013 and 2013/2014 academic years. One hundred nine final exams (at a ratio of two per subject) of the Medicine, Dentistry and Nursing programs were reviewed, for a total of 629 questions. The syllabi were analyzed, contrasting the objectives and skills with the contents to be examined. Results: The most common question format was the modified essay question requiring short answers. Of the 109 exams, 88.9 % had well-constructed stems, 59.6% well-designed items and 61.6% correct rating scales. The most frequent errors were omission of the subject or content in the stem of the questions; imprecise task in modified essay questions; and multiple-choice questions with a simple alternative to be selected out of three. Sixty four point seven percent of the questions involved reproduction of knowledge. Conclusion: most of the exams are properly designed, but there are some difficulties in the construction of questions and rating scales. The high percentage of questions aimed at reproducing knowledge was regarded as a weakness since they limit the conceptual validity.